2003
DOI: 10.1073/pnas.1233767100a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics and evolution of pheromone biosynthesis in Lepidoptera

Abstract: A great diversity of pheromone structures are used by moth species (Insecta: Lepidoptera) for long-distance mating signals. The signal͞ response channel seems to be narrow for each species, and a major conundrum is how signal divergence has occurred in the face of strong selection pressures against small changes in the signal. Observations of various closely related and morphologically similar species that use pheromone components biosynthesized by different enzymes and biosynthetic routes underscore the quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
119
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(125 citation statements)
references
References 60 publications
(46 reference statements)
2
119
1
Order By: Relevance
“…This selective partitioning is undoubtedly the result of the enzyme's bifunctionality and clearly demonstrates the divergence of the B. mori Desat1 from the other ⌬11 desaturases. Analysis of the other pheromone gland-derived desaturases indicates that desat4 can be clustered with ⌬9 desaturases, whereas desat5 can be grouped within the ⌬10,11 branch of desaturase genes (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This selective partitioning is undoubtedly the result of the enzyme's bifunctionality and clearly demonstrates the divergence of the B. mori Desat1 from the other ⌬11 desaturases. Analysis of the other pheromone gland-derived desaturases indicates that desat4 can be clustered with ⌬9 desaturases, whereas desat5 can be grouped within the ⌬10,11 branch of desaturase genes (20).…”
Section: Discussionmentioning
confidence: 99%
“…For other desaturase genes expressed in the pheromone gland, poly(A) ϩ RNA (300 ng) was prepared with the MICROFAST-TRACK 2.0 mRNA isolation kit (Invitrogen) and reversetranscribed with Oligo(dT) 20 by using the Thermoscript RT-PCR system (Invitrogen). To amplify DNA fragments of all of the desaturase genes present, a set of degenerate primers, DsF (5Ј-AT H ACNGCNGGNGCNCAYMG-3Ј) and DsR (5Ј-AANRYRTGRTGRTARTTRTG-3Ј), were designed from the conserved sequences encoding the first and third histidinecluster regions of known insect desaturases (4).…”
Section: Methodsmentioning
confidence: 99%
“…moths and butterflies), the successful propagation of individual species is dependent on the female's ability to attract conspecific males; an event mediated by species-specific blends of volatile compounds known as sex pheromones (1). These sex pheromones are produced and released by a specialized gland, appropriately known as the pheromone gland (PG), 1 located between the eighth and ninth abdominal segments of the female. A major class of pheromone components produced by female moths is the C 10 -C 18 unsaturated, acyclic, aliphatic compounds that contain an oxygenated functional group such as aldehyde, alcohol, or acetate ester.…”
mentioning
confidence: 99%
“…Biosynthesis of these blends involves three key enzymatic components: uncharacterized enzymes that mediate limited chainshortening reactions, reductases that convert acyl intermediates into alcohols, and sex pheromone desaturases that introduce double bonds at specific locations along the hydrocarbon chain. Moth sex pheromone desaturases are part of a larger family of insect acyl-CoA desaturases that originated several hundred Mya (1). So far, five distinct desaturase subfamilies have been discovered and found to function in the biosynthesis of female moth sex pheromone blends (2).…”
mentioning
confidence: 99%
“…Because sex pheromone desaturases are key players in moth reproduction, an understanding of the mechanisms that are responsible for generating their diversity may shed light on the molecular processes that underlie speciation in this group of insects. Thus, we initiated research to examine the diversity of sex pheromone desaturase genes and their patterns of evolution in the genomes of the ECB and ACB, two representative moth species for which a considerable amount of knowledge concerning their pheromone blends and chemical communication systems has been amassed over the past few decades (1,(4)(5)(6)(7)(8)(9). Surprisingly, we found that an even larger number of ''cryptic'' sex pheromone desaturase genes exist within corn borer genomes and that these novel genes were generated as a result of a fusion event with a retroposon.…”
mentioning
confidence: 99%